Dynamic mass redistribution analysis of endogenous β‐adrenergic receptor signaling in neonatal rat cardiac fibroblasts. Issue 1 (26th January 2014) - Carter, Rhonda L.; Grisanti, Laurel A.; Yu, Justine E.; Repas, Ashley A.; Woodall, Meryl; Ibetti, Jessica; Koch, Walter J.; Jacobson, Marlene A.; Tilley, Douglas G.
Abstract Label‐free systems for the agnostic assessment of cellular responses to receptor stimulation have been shown to provide a sensitive method to dissect receptor signaling. β‐adenergic receptors (βAR) are important regulators of normal and pathologic cardiac function and are expressed in cardiomyocytes as well as cardiac fibroblasts, where relatively fewer studies have explored their signaling responses. Using label‐free whole cell dynamic mass redistribution (DMR) assays we investigated the response patterns to stimulation of endogenous βAR in primary neonatal rat cardiac fibroblasts (NRCF). The EPIC‐BT by Corning was used to measure DMR responses in primary isolated NRCF treated with various βAR and EGFR ligands. Additional molecular assays for cAMP generation and receptor internalization responses were used to correlate the DMR findings with established βAR signaling pathways. Catecholamine stimulation of NRCF induced a concentration‐dependent negative DMR deflection that was competitively blocked by βAR blockade and non‐competitively blocked by irreversible uncoupling of Gs proteins. Subtype‐selective βAR ligand profiling revealed a dominant role for β2AR in mediating the DMR responses, consistent with the relative expression levels of β2AR and β1AR in NRCF. βAR‐mediated cAMP generation profiles revealed similar kinetics to DMR responses, each of which were enhanced via inhibition of cAMP degradation, as well as dynamin‐mediated receptor internalization. Finally, G protein‐independent βAR signaling through epidermal growth factor receptor (EGFR) was assessed, revealing a smaller but significant contribution of this pathway to the DMR response to βAR stimulation. Measurement of DMR responses in primary cardiac fibroblasts provides a sensitive readout for investigating endogenous βAR signaling via both G protein‐dependent and –independent pathways.